Understanding Fomalhaut as a Cooper pair. Issue 4 (5th December 2017) - Feng, F; Jones, H R A
Abstract: Fomalhaut is a nearby stellar system and has been found to be a triple based on astrometric observations. With new radial velocity and astrometric data, we study the association between Fomalhaut A, B, and C in a Bayesian framework, finding that the system is gravitationally bound or at least associated. Based on simulations of the system, we find that Fomalhaut C can be easily destabilized through combined perturbations from the Galactic tide and stellar encounters. Considering that observing the disruption of a triple is probably rare in the solar neighbourhood, we conclude that Fomalhaut C is a so-called 'gravitational pair' of Fomalhaut A and B. Like the Cooper pair mechanism in superconductors, this phenomenon only appears once the orbital energy of a component becomes comparable with the energy fluctuations caused by the environment. Based on our simulations, we find (1) an upper limit of 8 km s −1 velocity difference is appropriate when selecting binary candidates, and (2) an empirical formula for the escape radius, which is more appropriate than tidal radius when measuring the stability of wide binaries.